Chiuri (Aesandra butyracea) and Beekeeping for Sustainable Livelihoods of Chepang Community in Raksirang-6, Makawanpur, Nepal - Datendra Kumar Golay; Mahamad Sayab Miya; Sachin Timilsina (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Chiuri trees and beekeeping are the major sources of livelihood among the Chepang community. The study was performed to assess the role of Chiuri on livelihood improvement of the Chepang community through beekeeping and to analyze the efforts of CFUGs to conserve the Chiuri in Silinge Community Forest User Group, Raksirang-6, Makawanpur district, Nepal. Focus Group Discussion, Key Informant Survey and Individual interview in households were carried out for the study from January to March 2019. With the increasing demand for organic honey made from Chiuri, the locals of the Chepang village in Makawanpur have started generating a good income from beekeeping. The majority (63%) of the respondents reported that the trends of the status of beekeeping were increasing in households. The selling of honey was the main source of income for the people of Silinge CFUGs. 1/3 of households earned the money in the range of NRs 200,000 (US$ 1,720.83) - NRs 300,000 (US$ 2,581.24). Physical capital and financial capital have significantly increased, whereas human, social and natural capitals were in increasing trends. The relationship between Chiuri and honey bees was very positive for both. The marketing system of Chiuri is not well developed in the study area. The Chepang community will get more prices after certifying their products as organic. Organic Certification of Nepal (OCN) should conduct studies about organic honey.